Effect of Using Ceramic Backing Media on SMAW Welding on Value Reduction of Area on ASTM A36 Steel - Juswan Sade (Collaborate, 2023)
ASTM A36 steel is a low-carbon steel often used as a general manufacturing material. Tensile testing is one of the most important and dominant mechanical properties in construction design and manufacturing. Each material or material has different properties (hardness, flexibility, etc.). A test is needed to determine a material's mechanical properties. One of the most frequently performed tests is the tensile test. This test has a function to determine the level of strength of a material and to identify the characteristics of the material. Therefore, this study aims to determine the effect of using ceramic backing media in SMAW welding on the value of area reduction in ASTM A36 steel. Based on the test results, the value of the area reduction varies in each specimen. The specimens that did not use ceramic backing had an average area reduction value of 53.51%, while the variation using ceramic backing had an average area reduction value of 61.17%.